A new approach for optimum simultaneous multi-DG distributed generation Units placement and sizing based on maximization of system loadability using HPSO (hybrid particle swarm optimization) algorithm - Aman, M.M.; Jasmon, G.B.; Bakar, Ab Halim Abu; Mokhlis, Hazlie (Elsevier, 2014)
This paper presents a new approach for optimum simultaneous multi-DG (distributed generation) placement and sizing based on maximization of system loadability without violating the system constraints. DG penetration level, line limit and voltage magnitudes are considered as system constraints. HPSO (hybrid particle swarm optimization) algorithm is also proposed in this paper to find the optimum solution considering maximization of system loadability and the corresponding minimum power losses. The proposed method is tested on standard 16-bus, 33-bus and 69-bus radial distribution test systems. This paper will also compare the proposed method with existing Ettehadi method and present the effectiveness of the proposed method in terms of reduction in power system losses, maximization of system loadability and voltage quality improvement.